2011
DOI: 10.1258/ar.2010.100276
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of MR elastography in the diagnosis of prostate cancer at 3.0T

Abstract: MR elastography can be used to visualize the difference in stiffness between prostate cancer and benign prostatic disease. It is a new imaging method with potential in the diagnosis of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…Most studies rely on biopsy and sectioned whole mount slides as a gold standard (7,10). Unfortunately, in these methods the spatial information is lost and the researcher has to guess the location of the biopsy or the section of the whole mount from the pathology report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies rely on biopsy and sectioned whole mount slides as a gold standard (7,10). Unfortunately, in these methods the spatial information is lost and the researcher has to guess the location of the biopsy or the section of the whole mount from the pathology report.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MRE of human in vivo prostate cancer has been demonstrated by only two groups. Li et al (10) used a trans-pelvic excitation at 100 Hz with a 4 mm resolution and showed a positive correlation between biopsy cores graded by the Gleason score and elasticity of prostate cancer (r = 0.91, p < 0.01) in 18 patients. They found that mean elasticity was significantly higher in the lesions with prostate cancer (6.55 ± 0.47 kPa) than in regions with prostatitis (1.99 ± 0.66 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…MRI elastography technology was also developed (S. Li et al, 2011), but here only ultrasound is described. Back-scattered ultrasound waves are displaced with compression or decompression of tissue (approximately 2%), harder areas showing less displacement compared to softer (Salomon et al, 2008).…”
Section: Elastographymentioning
confidence: 99%
“…In vivo MRE has been successfully applied to reveal the stiffness of a variety of human tissues and organs such as the brain [4] [6], breast [4] [7], liver [4] [8], prostate [9] [10], and skeletal muscles [4] [10].…”
Section: Introductionmentioning
confidence: 99%